Rethinking Student Wellbeing in Higher Education: A Multifaceted Approach to Stress Management - Jinjing Fang; Xin Ren; Valerie Ann Sotardi (Education Sciences)
The increasing prevalence of psychological distress among students has prompted global concern about how educational systems might promote student wellbeing [...]